Analysis of Physiological and Transcriptomic Differences between a Premature Senescence Mutant (GSm) and Its Wild-Type in Common Wheat (Triticum aestivum L.) - Juan Lu; Lili Sun; Xiujuan Jin; Md Ashraful Islam; Feng Guo; Xiaosha Tang; Kai Zhao; Huifang Hao; Ning Li; Wenjun Zhang; Yugang Shi; Shuguang Wang; et al. (Biology, 2022)
Premature leaf senescence has a profound influence on crop yield and quality. Here, a stable premature senescence mutant (GSm) was obtained from the common wheat (Triticum aestivum L.) cultivar Chang 6878 by mutagenesis with ethyl methanesulfonate. The differences between the GSm mutant and its wild-type (WT) were analyzed in terms of yield characteristics, photosynthetic fluorescence indices, and senescence-related physiological parameters. RNA sequencing was used to reveal gene expression differences between GSm and WT. The results showed that the yield of GSm was considerably lower than that of WT. The net photosynthetic rate, transpiration rate, maximum quantum yield, non-photochemical quenching coefficient, photosynthetic electron transport rate, soluble protein, peroxidase activity, and catalase activity all remarkably decreased in flag leaves of GSm, whereas malondialdehyde content distinctively increased compared with those of WT. The analysis of differentially expressed genes indicated blockade of chlorophyll and carotenoid biosynthesis, accelerated degradation of chlorophyll, and diminished photosynthetic capacity in mutant leaves; brassinolide might facilitate chlorophyll breakdown and consequently accelerate leaf senescence. NAC genes positively regulated the senescence process. Compared with NAC genes, expression of WRKY and MYB genes was induced earlier in the mutant possibly due to increased levels of reactive oxygen species and plant hormones (e.g., brassinolide, salicylic acid, and jasmonic acid), thereby accelerating leaf senescence. Furthermore, the antioxidant system played a role in minimizing oxidative damage in the mutant. These results provides novel insight into the molecular mechanisms of premature leaf senescence in crops.